The Effect of Ease of Access and Market Reach on Used Goods Sales Revenue Through Facebook Marketplace in Yogyakarta City - Andres Rahmadani; Rinaldi Rinaldi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research was conducted in Yogyakarta. The goal is to find out how the sales revenue of sellers on Facebook Marketplace gets a large revenue affected by Ease of access and Market reach. 80 Yogyakarta locals who sell second-hand goods on the Facebook Marketplace participated in this study. The calculated t-value for the Ease of access variable was 2.134 > t table, or 1.191, with significant values of 0.036 and < 0.05, according to the researchers' findings. This indicates that sales revenue is affected by the Ease of access variable. The t-value calculated by the researcher for the variable Market reach was 2.402 > t table, or 1.191, with a significant value of 0.009 and > 0.05, according to the findings of this study showing that sales revenue is influenced by market reach. And it was found that 12,294 > 3,115 are the F-values calculated > from table F. This shows that the Ease of access and market reach factor drives customers' desire to make purchases on Facebook Marketplace which affects the amount of sales revenue of second-hand sellers on Facebook Marketplace.